Suplementasi L-Karnitin dan Asam Lemak PUFA Terproteksi dalam Ransum Limbah Pasar Organik Terfermentasi Pengaruhnya Terhadap Komposisi Kimiawi Air Susu Kambing - Sudibya, Sudibya; Hanifa, Aqni; Handayanta, Eka; Intansari, Ayu; Hadi, Rendi Fathoni (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
The experiment was conducted to investigate the effect of transfer protection PUFA and L-carnitin on the ration on chemist composition of dairy milk In total, 15 female dairy goats of 2-4 year this old Peranakan Etawah (PE) with body weight of 25-55 kg were used in this experiment. The assay diets included a basal diet (control) based on yellow corn, rice bran, soy bean meal and coconut meal, mineral, tuna fish oil and lemuru fish oil. The method of the research was experimental in vivo using Completely Randomized Blok Design (RAK). There were 5 treatment in each treatment and 3 replication. Treatment consisted of P0 = control ration, P1 = P0 +50% market waste subtition grass on the ration, P2 = P1+500 ppm L-karnitin on the ration, P3 = P1+protection tuna fish oil 5% in the ration and P4 = P1+ protection lemuru fish oil 5% in the ration. The variables measuared content composition dairy milk goat. The results of variance analysis showed that the effect of suplementation protection PUFA in the rations on market waste contain 500 ppm L-carnitine were significantly (P<0.01) of acid goats milk composition. The conclusion of this research shows that the suplementation protection PUFA in the ration contain 500 ppm L-carnitine, can decrease milk cholesterol from 0,482% to 0,420%, LDL from 45,30 to 33,13 mg/dl. There for to increase HDL from 54,70 to 66,87 mg/dl, omega-3 fatty acid from 1,10% to 4,04%, omega-6 fatty acid from 1,46% to 18,80 percent. Keywords: composition dairy milk goats, L-carnitine, protection PUFA fatty acid